Enhancing Quality of Service in Software-Defined Internet of Things (SD-IoT) Environment: A review - Grif Abdelali; Zyane Abdellah (ITM Web of Conferences)
The Internet of Things (IoT) connects billions of devices via the Internet, providing real-time intelligent services. Software-Defined Networking (SDN) represents an advanced solution for managing traffic and resources in these IoT environments, enabling centralized and flexible management through the separation of control and data. This article provides an in-depth analysis of current approaches to addressing Quality of Service (QoS) challenges in SD-IoT networks. It examines specific techniques such as QoS routing, dynamic load balancing, real-time traffic classification, and adaptive rule placement, highlighting key results such as improved efficiency of QoS routing algorithms and the benefits of load balancing strategies based on heuristic optimization. The article also identifies persistent challenges, such as issues related to scalability. Finally, it proposes future research directions, including the integration of artificial intelligence to enhance the adaptability of management models and address the growing complexities of SD-IoT networks.